1997
DOI: 10.1128/aem.63.2.803-805.1997
|View full text |Cite
|
Sign up to set email alerts
|

Novel group within the kingdom Crenarchaeota from boreal forest soil

Abstract: We report here the results of phylogenetic analysis of archaeal 16S rRNA gene sequences amplified by PCR with Archaea-specific primers with mixed-population DNA extracted directly from forest soil used as a template. Nucleotide signature and phylogenetic analyses show that the sequences obtained belong to the domain Archaea and form a new cluster. Its phylogenetic position suggests that sequences are from a previously undescribed terrestrial group within the kingdom Crenarchaeota.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
147
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(160 citation statements)
references
References 21 publications
11
147
1
1
Order By: Relevance
“…Andrews soils and between tree types. Other research has also shown that archaeal populations may vary between soil types and plant communities (Jurgens et al, 1997;Ochsenreiter et al, 2003;Nicol et al, 2007). Further research is needed to determine if differences in AOA distribution, population size and community composition contribute to the increased rates of NH 3 oxidation that we observed in soils at Cascade Head and in the presence of red alder.…”
Section: Discussionmentioning
confidence: 76%
“…Andrews soils and between tree types. Other research has also shown that archaeal populations may vary between soil types and plant communities (Jurgens et al, 1997;Ochsenreiter et al, 2003;Nicol et al, 2007). Further research is needed to determine if differences in AOA distribution, population size and community composition contribute to the increased rates of NH 3 oxidation that we observed in soils at Cascade Head and in the presence of red alder.…”
Section: Discussionmentioning
confidence: 76%
“…Polymerase chain reaction products were obtained using primers Ar3F (Giovannoni et al, 1988) and Ar9R (Jurgens et al, 1997) (Table 1) generating a PCR product approximately 900 bp in length. For DGGE analysis, these PCR products were used as template in a nested PCR reaction using primers rSAf/PARCH519r (Table 1) generating a PCR product 118 bp in length (excluding primers).…”
Section: Nucleic Acid Extraction and Rt-pcr Amplification Of Archaealmentioning
confidence: 99%
“…Organisms belonging to the largely non-thermophilic 'Group 1' Crenarchaeota lineage appear to be ubiquitous in soil systems including grassland, forest, agricultural and rice field soils (e.g. Bintrim et al ., 1997;Jurgens et al ., 1997;Buckley et al ., 1998;Großkopf et al ., 1998;Nicol et al ., 2003a) and may be dominant over euryarchaeal populations in grassland soils (Nicol et al ., 2003b). Despite an increasing understanding of crenarchaeal diversity in the environment, little is known about the drivers of crenarchaeal diversity and their ecological functioning in soil systems (Nicol et al ., 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Amplification 16S rRNA genes from Archaea for DGGE analysis using other general PCR primers (Ar3F, Ar9F; Jurgens et al, 1997) was also only successful with the 4.15 mbsf sediment. Therefore, nested PCR was applied Euryarchaeota Methane using marine sediment NANK-A-GW-56 Uncultured Archaea clone 33-FL49A00 (AF355958) 91 Crenarchaeota Mid-ocean ridge sediment a. Sequences named NANK-B-GW-nn are from the bands in Fig.…”
Section: Diversity Of Archaeamentioning
confidence: 99%
“…Primary amplification reactions for Bacteria were as described above. Amplification reaction mixtures for Ar3f, Ar9r were with primer pair 21F, 958R using PCR conditions as described in Jurgens et al (1997). Secondary PCR amplification (Bacteria 357F-GC, 518R, and Archaea SAf, PARCH 519R) were carried out without BSA in a 50 ml reaction mix (Webster et al, 2003).…”
Section: Pcr Reaction Conditionsmentioning
confidence: 99%